Risk management committee, ownership concentration and hedging activities disclosure : evidence of Malaysian companies - Abdullah, Azrul (2016)
Although the listed companies on Bursa Malaysia began to report their hedging activities under the Malaysian Financial Reporting Standard (MFRS) 7, 132 and 139 in 2010, there has been no clear and adequate evidence on information of hedging activities using derivatives. This matter prompted this study to examine the extent of information on hedging activities disclosure (HAD). This study also examined the role of the Risk Management Committee (RMC) and its effectiveness in influencing the extent of HAD. Furthermore, this study examined the moderating effect of ownership concentration on the relationship between the effectiveness of the RMC and the extent of HAD. Data were collected from the annual reports of 500 non-financial listed companies on Bursa Malaysia in 2013. This study used descriptive, multiple, and hierarchical regression to analyse the data. The analyses show that the extent of HAD by non-financial companies in Malaysia is insufficient. This study finds that large and high leverage companies tend to provide more HAD in their annual reports, but the existence of RMC does not affect the extent of HAD. Besides, the findings of this study reveal that the relationship between the effectiveness of RMCs is negatively associated with the extent of HAD. However, when the characteristics of the RMC are individually tested, it is found that only RMC independence and diligence have an influence on the extent of HAD. The findings also show that high ownership concentration does not significantly moderate the relationship between RMC effectiveness and the extent of HAD. This study provides empirical evidence on the extent of HAD in Malaysia and also the importance of the existence and effectiveness of RMCs in enhancing the quality of financial reporting in the country, which will be useful for investors, policy-makers, regulators and researchers.